Relationship Between Knowledge of Contraception Acceptors with Sede Effects of the Three Month Injection Family Planning in Kambesko Health Center 2017 - Venny Rismawanti (Universitas Andalas, 2019)
Countries Indonesia in 2015 is the country with the number of residents of the largest fourth in the world after China, India and the United States with the number of people reaching 255 461 686 inhabitants. In the year 2018, the number of population of Indonesia is growing rapidly to reach the number 365 015 313 inhabitants and the explosion of the population have led to burden the country is getting increased.Objective: To determine the relationship between knowledge of family planning acceptors and side effects of 3-month family planning injection in the Kambesko Community Health Center 2017.Method: This was analytic study with consecutive sampling technique.Results: The results of this study conducted at the Kambesko Health Center were obtained from 85 sample stating that the knowledge of family planning acceptors about the side effects of 3-month family planning injections divided into 2 categories, which are : good 21 people (25%), limited 64 people (75%), and those who experienced side effects of 60 people (71%), and who did not experience side effects of 25 people (29%).Conclusion: It can be concluded that there is a relationship between the knowledge of family planning acceptors and the side effects of 3-month family planning injection at the Kambesko Health Center in 2017 with a p value (0.04).